2015
DOI: 10.1371/journal.ppat.1004642
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Heterologous Primary Infections Radically Alter Immunodominance Hierarchies and Clinical Outcomes Following H7N9 Influenza Challenge in Mice

Abstract: The recent emergence of a novel H7N9 influenza A virus (IAV) causing severe human infections in China raises concerns about a possible pandemic. The lack of pre-existing neutralizing antibodies in the broader population highlights the potential protective role of IAV-specific CD8+ cytotoxic T lymphocyte (CTL) memory specific for epitopes conserved between H7N9 and previously encountered IAVs. In the present study, the heterosubtypic immunity generated by prior H9N2 or H1N1 infections significantly, but variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 67 publications
6
29
0
1
Order By: Relevance
“…Both memory CD4 + and CD8 + T cells are able to protect mice from a lethal IAV infection in the absence of any other immune cell population (14,23,85), and the size of the memory T cell compartment is a good correlate of protection against a secondary heterologous infection (86,87). In humans, survival from a new influenza strain depends on the presence of memory CD8 + T cells (17,18), and in a rechallenge study, the numbers of CD4 + T cells directed against internal proteins correlated with lower viral titers and weaker symptoms (17).…”
Section: Development Of Iav-specific Memory T Cell Responsesmentioning
confidence: 99%
“…Both memory CD4 + and CD8 + T cells are able to protect mice from a lethal IAV infection in the absence of any other immune cell population (14,23,85), and the size of the memory T cell compartment is a good correlate of protection against a secondary heterologous infection (86,87). In humans, survival from a new influenza strain depends on the presence of memory CD8 + T cells (17,18), and in a rechallenge study, the numbers of CD4 + T cells directed against internal proteins correlated with lower viral titers and weaker symptoms (17).…”
Section: Development Of Iav-specific Memory T Cell Responsesmentioning
confidence: 99%
“…When mice that have recovered from a primary influenza infection are re-infected with a heterologous IAV (a strain with different surface glycoproteins but the same internal proteins) that is resistant to neutralization by antibody induced by the primary infection, influenzaspecific CD8 + T cells are responsible for accelerated viral clearance and reduced disease burden [13,[59][60][61]. Studies in guinea pigs also demonstrated that priming with the 2009 pandemic H1N1 virus confers protection against the 2013 avian H7N9 IAV [62].…”
Section: Cd8 + T Cells Confer Cross-protection Across Different Influmentioning
confidence: 99%
“…Dramatic shifts in the immunodominance hierarchy upon heterosubtypic infection have also been observed for CD8 T cells. [71][72][73] Previously activated CD4 T cells are known to require lower epitope density to become reactivated and also to expand more rapidly than naive CD4 T cells. [74][75][76][77] Our later studies showed that the advantage that is afforded to memory CD4 T cells specific for internal virion proteins, at the expense of CD4 T cells specific for HA, could be overcome by an intermediate boost with HA-derived peptides derived from the second virus.…”
Section: The S Pecifi Cit Y Of CD 4 T Cell S To Influ Enz a Virusmentioning
confidence: 99%